Case report: Stent-first strategy as a potential approach in the management of malignant right-sided colonic obstruction with cardiovascular risks - Lin, Tianyu; Bissessur, Abdul Saad; Liao, Pengfei; Yu, Tunan; Chen, Dingwei (Frontiers in Surgery, 2022)
In obstructing left-sided colonic or rectal cancer, endoscopic stent placement with the purpose of decompression and bridge to elective colon resection has been widely utilized and accepted. However, in malignant right-sided colonic obstruction, stent placement prior to colectomy is still highly controversial, due to lower clinical success and high anastomotic leak. We report a case of malignant right-sided colonic obstruction based on the radiological findings of irregular thickening of ascending colon wall and dilation of proximal large bowel on enhanced computed tomography scan. The 72-year-old woman presented with obvious abdominal distension. Due to concerning cardiovascular complications as intermittent chest pain and a long history of type 2 diabetes, a three-step therapeutic plan was instigated. Initially, a self-expandable metallic stent was placed palliatively to relieve the bowel obstruction. Consecutively, coronary angiography was performed, and two coronary stents were implanted to alleviate more than 80% stenosis of two main coronary arteries. One month later, laparoscopic radical resection of right colon and lymphadenectomy were successfully performed, with a blood loss less than 50 millimeters and a harvest of 29 lymph nodes, 1 being positive. The patient was discharged one week postoperatively with no complications, and received adjuvant chemotherapy one month later. During a follow-up of more than one year, the patient was in complete remission with no recurrence and cardiovascular events. In patients presenting with malignant right-sided colonic obstruction and peril of high cardiovascular risks, we propose colonic and coronary stent-first strategy to emergency surgery as a potential approach so as to ensure sufficient cardiovascular preparation improving perioperative safety. Moreover, the anatomical location of the tumor would be significantly achievable thus granting high-quality radical colon resection and lymphadenectomy.